2003
DOI: 10.1016/j.cub.2003.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Itk Functions to Control Actin Polymerization at the Immune Synapse through Localized Activation of Cdc42 and WASP

Abstract: Actin polymerization at the immune synapse is required for T cell activation and effector function; however, the relevant regulatory pathways remain poorly understood. We showed previously that binding to antigen presenting cells (APCs) induces localized activation of Cdc42 and Wiskott-Aldrich Syndrome protein (WASP) at the immune synapse. Several lines of evidence suggest that Tec kinases could interact with WASP-dependent actin regulatory processes. Since T cells from Rlk-/-, Itk-/-, and Rlk-/- x Itk-/- mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
102
1
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 31 publications
12
102
1
1
Order By: Relevance
“…We have previously reported that Itk-deficient cells show defective TCR-induced actin polarization that is associated with decreased activation of Cdc42, a key regulator of the WiskottAldrich syndrome protein (19). We additionally found that Vav was not properly targeted to the site of TCR contact.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…We have previously reported that Itk-deficient cells show defective TCR-induced actin polarization that is associated with decreased activation of Cdc42, a key regulator of the WiskottAldrich syndrome protein (19). We additionally found that Vav was not properly targeted to the site of TCR contact.…”
Section: Discussionmentioning
confidence: 86%
“…T cell/bead conjugates were stained with Alexa594-phalloidin (Molecular Bioprobes) as described previously (19). For Vav localization, cells were stained with anti-FLAG (1:500 in 1.25% BSA/0.1% saponin in PBS at room temperature for 40 min), followed by two washes and incubation with a solution of FITC-anti-mouse IgG (1:1000) and Alexa594-phalloidin (1: 67) (19).…”
Section: Immunofluorescence Staining and Microscopymentioning
confidence: 99%
See 3 more Smart Citations